Social issues of women in the contemporary Islamic schools - Prof. Dr. Muhammad Hussein Ali Al-Sweiti; Dr. Hamdiya Saleh (Journal of College of Education, 2023)
The local role of women in Iraq in the process of socio-economic construction has clearly emerged after 2003, as an extension of her international role confirmed by civil society and human rights organizations in the Arab and international world, which emphasized the importance of the role of women in establishing peace and their importance in economic empowerment in recovery policies It contributes significantly to the effectiveness of economic activities and economic growth in the post-2003 period, and leads to an improvement in the quality of measures and policies for economic recovery and their social results and to the achievement of sustainable development. the dispute. The issue of the social and economic role of women is one of the topics that have received the attention of all economic, social, and even political components as far as their interests are concerned, as this period of time witnessed a remarkable development in discussing women’s issues and giving them a progressive character by linking them to important issues at the international level such as the rights of women Man, socio-economic development, combating terrorism, armed conflicts and violence, and economic and political reform, which in turn contribute to the issue of achieving world peace, which is the supreme goal of developed nations.